Room Enough : Bilder und Objekte - Sammlung Schürmann. - Grimme, E.G. (Aachen : Suermondt-Ludwig-Museum Aachen, 1987)
Kawara, On ; Oehlen, Albert ; Meuser ; Kasseböhmer, Axel ; Mucha, Reinhard ; Kippenberger, Martin ; Herold, Georg ; Trockel, Rosemarie ; Kiecol, Hubert ; Federle, Helmut ; Daniels, René ; Dahn, Walter ; Förg, Gunther ; Holzer, Jenny ; Linke, Simon
Room Enough : Bilder und Objekte - Sammlung Schürmann, Suermondt-Ludwig-Museum, Aachen, 9. August - 20. September 1987
Duits
boek